Intrinsic and Extrinsic Determinants of T Cell Metabolism in Health and Disease - Munford, Haydn; Dimeloe, Sarah (Frontiers in Molecular Biosciences, 2019)
T lymphocytes are a critical component of the adaptive immune system, with key roles in the immune response to infection and cancer. Their activity is fundamentally underpinned by dynamic, regulated changes in their metabolism. This ensures adequate availability of energy and biosynthetic precursors for clonal expansion and effector function, and also directly regulates cell signalling, gene transcription and protein translation. In health, distinct T cells subtypes demonstrate differences in intrinsic metabolic capacity which correlate with their specialised immune functions. In disease, T cells with impaired immune function appear to be likewise metabolically impaired. Furthermore, diseased tissue environments -through inadequate provision of nutrients and oxygen, or accumulation of metabolic intermediates, end-products and cytokines- can impose metabolic insufficiency upon these cells, and further compound intrinsic impairments. These intrinsic and extrinsic determinants of T cell metabolism and their potential compound effects, together with the mechanisms involved form the subject of this review. We will also discuss how dysfunctional metabolic pathways may be therapeutically targeted to restore normal T cell function in disease.